Physiological and biochemical responses of apple trees to irrigation water depth in a semiarid region of brazil - de Oliveira, Cíntia Patrícia Martins [UNESP]; Simões, Welson Lima; da Silva, José Aliçandro Bezerra; Faria, Glaucia Amorim [UNESP]; Lopes, Paulo Roberto Coelho; Amorim, Magno Do Nascimento (FapUNIFESP (SciELO), 2020)
The present study evaluated the physiological and biochemical parameters of apple trees under different irrigation water depths in a semiarid region of Brazil. The experiment had a split-plot randomized block design. Irrigation levels (60, 80, 100, and 120% of the reference evapotranspiration-ET0) and two apple cultivars (Julieta and Princesa) were analysed in the experimental plots and the phenological stages (vegetative, flowering and fruiting) were analysed in the experimental subplots. The physiological characteristics evaluated included the chlorophyll index, relative water content, net photosynthesis, stomatal conductance, transpiration, internal CO2 concentration, leaf temperature and instant carboxylation efficiency. The biochemical characteristics evaluated included the leaf contents of reducing sugars, total soluble sugars, and non-reducing sugars and proteins. The best biochemical responses were observed in the Princesa cultivar under 80% ET0 during the flowering and vegetative stages and under 120% ET0 during the fruiting stage. The best physiological responses for all phenological stages were observed under irrigation levels of 120% ET0 for both cultivars. The cv. Princesa demonstrated osmotic adjustment under water stress conditions during the phenological stages evaluated.
Respostas fisiológicas e bioquímicas de macieiras sob lâminas de irrigação no semiárido brasileiro
Keywords: Gas exchange; Index terms: Malus domestica; Leaf carbohydrates; Physiological stages